Marketing Communications and Environmental Turbulence: A Complexity Theory View - Mason, Roger B. (Journal of Economics and Behavioral Studies, 2014)
This paper investigates how the choice of different marketing communications activities is influenced by the nature of the company’s external environment, when viewing the environment through a complexity theory lens. A qualitative, case method, using depth interviews, investigated the marketing communications activities in four companies in order to identify the promotional activities adopted in more successful firms in turbulent and stable environments. The results showed that the more successful company, in a turbulent market, subtly uses some destabilizing promotional activities but also makes use of some stabilizing promotional activities. This paper is of benefit by emphasizing a new way to consider promotional activities in companies.